Valorization of bio-residues from the processing of main portuguese fruit crops: from discarded waste to health promoting compounds - Pascoalino, Liege (2021)
Food processing generates a large amount of bio-residues, which have become the focus of different studies aimed at valorizing this low-cost source of bioactive compounds. High fruit consumption is associated with beneficial health effects and, therefore, bio-waste and its constituents arouse therapeutic interest. The present work focuses on the main Portuguese fruit crops and revises (i) the chemical constituents of apple, orange, and pear pomace as potential sources of functional/bioactive compounds; (ii) the bioactive evidence and potential therapeutic use of biowaste generated in the processing of the main Portuguese fruit crops; and (iii) potential applications in the food, nutraceutical, pharmaceutical, and cosmetics industries. The current evidence of the effect of these bio-residues as antioxidant, anti-inflammatory, and antimicrobial agents is also summarized. Conclusions of the revised data are that these bio-wastes hold great potential to be employed in specific nutritional and pharmaceutical applications.